Digital object in neonatal nursing: impact on student learning - Natália Del'Angelo Aredes; Fernanda dos Santos Nogueira de Góes; Marta Angélica Iossi Silva; Marlene Fagundes Carvalho Gonçalves; Luciana Mara Monti Fonseca (Universidade Federal de Goias, 2015)
The study compared the cognitive learning of nursing students about clinical evaluation of premature, dividing them among those who used and did not use the learning digital object (LDO) as support material. Besides, it assessed the students' opinion about the LDO. The quasi-experiment was conducted in the infant health discipline of a Nursing course, in which 22 students participated divided as control group (n = 10) and experimental group (n =12). There was no significant statistical difference between groups, but the intra-group comparison for performance demonstrated significant difference in both, showing positive learning effects. Regarding students' opinion, very satisfying assessments were obtained about the digital object and its characteristics of interaction with the user. Although there was no significant impact between groups, the positive assessment from students' use reflects its importance as innovative didactic strategy and motivation for the students.